Are you Puffing your Children's Future Away? Energy Poverty and Childhood Exposure to Passive Smoking - Kushneel Prakash; Sefa Awaworyi Churchill; Russell Smyth (Global Labor Organization (GLO), 2022)
We examine whether having a parent who smoked during one's childhood or adolescence increases the probability of being in energy poverty in adulthood. We find that people who had a parent who smoked when they were young are 0.8 to 1.4 percentage points more likely to be in energy poverty later in life. Various checks suggest that this relationship can be regarded as being plausibly causal. We identify health, human capital, labour market outcomes and non-cognitive traits as channels through which early life exposure to passive smoking increases the likelihood of being in energy poverty. Our results have important implications for early life interventions to address the deficits caused by exposure to passive smoking.
Keywords: Q41; I32; 330; energy poverty; fuel poverty; smoking; early life shocks; Australia